Activities and Nurses' Role in Empowering Parents on Treating Children with Cancer - Rasmita, Dina (Universitas Aisyah Pringsewu, 2021)
Children with cancer will hospitalize for a long time, so it takes the role of the family as an integral part that cannot be separated from the child. The family are a partner in childcare. Family-centred care is an important part of childcare because the parent is a source of strength and a supportive child. The point of family-centred care is empowering families in childcare. Empowerment is the most important part of caring for nurses, families, and patients. Nurses are not only involved in daily childcare but also nurse plays a role in empowering parents in caring for children with cancer. The study aims to explore the activities and roles of nurses in empowering parents to care for children with cancer based on the nurse perception. The research design was a qualitative design with a phenomenological approach. Participants involved in this study were six nurses who served in the childcare room with cancer selected by purposive sampling technique. Data were collected by in-depth interview method using semi-structured interview guidelines. Data analysis with the analysis stage according to Colaizzi. The results of this study found four themes about the activities and roles of nurses in empowering parents in caring for children with cancer, including providing education, providing support, involving parents in caring for children, involving parents in decision making. Nurses can provide support according to the needs of parents and increase collaboration with parents in caring for children. Abstrak: Anak dengan kanker akan menjalani hospitalisasi dalam jangka waktu yang lama, sehingga dibutuhkan peran keluarga sebagai bagian integral yang tidak terpisahkan dari anak. Keluarga adalah mitra dalam perawatan anak. Perawatan berfokus pada keluarga adalah bagian penting dalam perawatan anak karena orangtua merupakan kekuatan dan dukungan utama bagi anak. Inti dari perawatan berfokus pada keluarga (PBK) adalah memberdayakan keluarga dalam perawatan anak. Pemberdayaan merupakan bagian terpenting dalam keperawatan baik untuk perawat, keluarga, dan pasien. Perawat tidak hanya terlibat dalam perawatan anak sehari-hari, tetapi perawat juga berperan dalam melakukan pemberdayaan orangtua dalam merawat anak dengan kanker. Penelitian ini bertujuan mengeksplorasi aktivitas dan peran perawat dalam pemberdayaan orangtua merawat anak dengan kanker berdasarkan sudut pandang perawat. Desain penelitian ini adalah desain kualitatif dengan pendekatan fenomenologi. Partisipan yang terlibat dalam penelitian ini adalah enam orang perawat yang bertugas di ruang perawatan anak dengan kanker dipilih dengan teknik purposive sampling. Pengambilan data dilakukan dengan metode wawancara mendalam menggunakan pedoman wawancara semi terstruktur. Analisis data dengan tahapan analisis menurut Colaizzi. Hasil penelitian ini menemukan empat tema tentang aktivitas dan peran perawat dalam pemberdayaan orangtua dalam merawat anak dengan kanker di antaranya yaitu memberi edukasi, memberi dukungan, melibatkan orangtua dalam merawat anak, melibatkan orangtua dalam pengambilan keputusan. Perawat dapat memberi dukungan sesuai dengan kebutuhan orangtua dan meningkatkan kolaborasi dengan orangtua dalam merawat anak.